METHOD FOR PRODUCING GRAIN-ORIENTED ELECTRICAL STEEL SHEET - OKUMURA Shunsuke; IMAI Takeshi (2022)
A method for producing a grain-oriented electrical steel sheet which has an intermediate layer containing silicon oxide as a main component on a surface of a base steel sheet in which a forsterite film is substantially absent and has an insulation coating on a surface of the intermediate layer includes: a decarburization annealing process of obtaining a decarburization-annealed steel sheet which has the oxygen content or 320 ppm or less and the carbon content of 25 ppm or less by subjecting a cold rolled steel sheet containing Si to decarburization annealing; a final annealing process of heating the decarburization-annealed steel sheet in a state in which a surface of the decarburization-annealed steel sheet is coated with an annealing separator to subject a steel sheet to secondary recrystallization; a removal process of obtaining a finally-annealed steel sheet by removing the annealing separator on the steel sheet which has been subjected to the final annealing process; an intermediate layer forming process of forming the intermediate layer by subjecting the finally-annealed steel sheet to thermal oxidation annealing; and an insulation coating forming process of forming the insulation coating on the finally-annealed steel sheet having the intermediate layer formed thereon.